Long‐Cycling Sulfide‐Based All‐Solid‐State Batteries Enabled by Electrochemo‐Mechanically Stable Electrodes. Issue 24 (10th May 2022) - Cao, Daxian; Sun, Xiao; Li, Yejing; Anderson, Alexander; Lu, Wenquan; Zhu, Hongli
Abstract: The anode plays a critical role relating to the energy density in all‐solid‐state lithium batteries (ASLBs). Silicon (Si) and lithium (Li) metal are two of the most attractive anodes because of their ultrahigh theoretical capacities. However, most investigations focus on Li metal, leaving the great potential of Si underrated. This work investigates the stability, processability, and cost of Si anodes in ASLBs and compares them with Li metal. Moreover, single‐crystal LiNi0.8 Mn0.1 Co0.1 O2 is stabilized with lithium silicate (Li2 SiO x ) through a scalable sol–gel method. ASLBs with a cell‐level energy density of 285 Wh kg −1 are obtained by sandwiching the Si anode, the thin sulfide solid‐state electrolyte membrane, and the interface stabilized LiNi0.8 Mn0.1 Co0.1 O2 . The full cell delivers a high capacity of 145 mAh g −1 at C/3 and maintains stability for 1000 cycles. This work inspires commercialization of ASLBs on a large scale with exciting manufacturing lines for large‐scale, safe, and economical energy storage. Abstract : Aiming at fabricating high‐performance all‐solid‐state lithium batteries (ASLBs), this work reports a silicon composite anode that demonstrates high capacity and better electrochemo‐mechanical stability than Li‐metal anodes. Meanwhile, interface‐stabilized single‐crystal LiNi0.8 Mn0.1 Co0.1 O2 is utilized as the cathode. The ASLB delivers a cell‐level energy density of 285 mAh g −1 and long cycling life of 1000 cycles.